2014
DOI: 10.1007/s00348-014-1822-5
|View full text |Cite
|
Sign up to set email alerts
|

Velocity field and parametric analysis of a subsonic, medium-Reynolds number cavity flow

Abstract: Cavity flows are a class of flows bounded by material structures, where a recirculation region is present, and they are found in many practical applications. In the present study, the interaction between a boundary layer and an open parallelepipedic cavity develops a Kelvin-Helmholtz-like instability coupled with the cavity recirculation. PIV measurements of the flow are carried out in two orthogonal planes inside the cavity, for different aspect ratios, incompressible flow conditions, and Reynolds numbers in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…This is in contrast to the complex internal flow topology observed in rectangular open cavity flows, e.g. Faure et al (2006); Faure (2014), where secondary separation is a relevant feature, and affects remarkably the shear layer dynamics, Kuo and Huang (2001). Rigorous results, Bunyakin et al (1998), show that a region of the wall with adverse pressure gradient has to exist in a vortex cell.…”
Section: Flow Visualisationsmentioning
confidence: 51%
“…This is in contrast to the complex internal flow topology observed in rectangular open cavity flows, e.g. Faure et al (2006); Faure (2014), where secondary separation is a relevant feature, and affects remarkably the shear layer dynamics, Kuo and Huang (2001). Rigorous results, Bunyakin et al (1998), show that a region of the wall with adverse pressure gradient has to exist in a vortex cell.…”
Section: Flow Visualisationsmentioning
confidence: 51%
“…It was observed that two primary mechanisms with distinctly different characteristic frequencies would influence the vorticity flux and generation as well as the pressure variations around the trailing edge corner. Recently, Faure et al (Faure 2014) investigated the flow morphology inside the cavity for various aspect ratios, impressible flow conditions and Reynolds numbers with the mean velocity and second-order moments of velocity fluctuations.…”
Section: Introductionmentioning
confidence: 99%